Nitrobenzene poisoning with methemoglobinemia (Indian Journal of Case Reports, 2019)
Nitrobenzene is a rarely encountered poison in clinical practice. Methemoglobinemia associated with the poisoning can be fatal. Early identification of methemoglobinemia and treatment with methylene blue and supportive measures can prevent mortality. However, hemolysis can be an outcome of treatment with methylene blue. Here, we report the case of nitrobenzene poisoning in a 35-year-old male which was treated successfully.